A proposed optimized equivalent circuit and performance analysis of dielectric barrier discharge ozone generator - Mohamed El_Hanash; Mohamed I. Youssef; Magdy M. Zaky (Institute of Advanced Engineering and Science, 2023)
Traditionally, low-frequency power supplies are used in dielectric barrier discharge (DBD) ozone generators. These generators require a very high output voltage. This may limit ozone production due to limitations imposed by the dielectric strength of the insulating material. Low-frequency generators also present low efficiency, large volumes, and difficulty in controlling ozone production. On the other hand, the advantages of high frequency DBD ozone generators are the increased power density applied to the chamber electrodes, and the voltage applied to the ozone chamber decreases, allowing for higher ozone production efficiency. From this point of view, in order to enhance and control the DBD ozone generator operating at high frequency, it is necessary to determine all parameter values and optimize the equivalent model for this type of generator. This work presents and proposes the practical methodologies used to extract all parameters of the high voltage high frequency (HVHF) transformer which can be used in these systems. Resonant frequency control techniques are presented in this paper. Elimination of the stray capacitance effect will also be implemented in this paper.